Policy Bubbles. Issue 1 (February 2014) - Jones, Bryan D.; Thomas, Herschel F.; Wolfe, Michelle
<x xml:space="preserve">Abstract</x> We develop the concept of a policy bubble to capture the notion of long‐term overinvestment in a policy. In sketching the relation of policy bubbles to economic bubbles, we describe how these two concepts have similar origins but different trajectories because they are filtered by different institutions. We examine in some detail three likely instances of ongoing policy bubbles: crime policy, school reform (charter schools and private education vouchers), and the contracting and privatization of public services. We show how these cases differ from the housing bubble of 1997–2007, how they differ from each other, and the extent to which they can be considered policy bubbles. Last, we suggest this concept can help unify the policy process literature with the practice of policy evaluation and outline testable hypotheses for future research.